Case report: Interdisciplinary management of a complex odontoma with a periapical involvement of superior anterior teeth [version 1; peer review: 2 approved] - Orozco, Esteban Isaí Flores [UNESP]; Hasna, Amjad Abu [UNESP]; de Santos Junior, Moacir Teotonio [UNESP]; Orozco, Elan Ignacio Flores; Do Prado, Renata Falchete [UNESP]; Campos, Gabriel Rocha; Valera, Marcia Carneiro [UNESP] (F1000Research, 2019)
This case report aims to describe the management of a complex odontoma with endodontic involvement of surrounding teeth utilizing a new bioceramic cement consisting of five mineral oxides (5MO) as a retro-filling material. The patient presented for routine consultation with slight dental mobility in the antero-superior region. Upon clinical and computed tomography examination, bone rarefaction was observed in the apical region of teeth 11 and 12, external root resorption in the involved teeth and necrotic pulp of tooth 12. Root canal treatment was performed in teeth 11 and 12. Later, local surgical excision of the lesion was carried out, finding a mass with clinical features of complex odontoma, with histopathological examination of the mass confirming this diagnosis. Retro-filling of tooth 12 with 5MO was carried out. No signs and symptoms were observed over twelve-months of follow-up, with bone neoformation observed in the region. Therefore, 5MO appears to be an effective bioceramic cement that has reparative features.
Keywords: Bioceramics; Complex odontoma; Computed tomography; Five mineral oxides